Factors contributing to university dropout: a review - Lorenzo-Quiles, Oswaldo; Galdón-López, Samuel; Lendínez-Turón, Ana (Frontiers in Education, 2023)
Introduction Dropout is one of the problems that the university education system has to face every year. The educational community is involved in the reasons for its trajectory as a social problem, which does not exempt any student in the world. Its study and improvement of the education system is a key element in changing the course of university dropout and alleviating its rapid growth in society. Methodology Using a quantitative and qualitative methodology, an attempt is made to provide answers to the objectives pursued by the research. Objectives To analyze student satisfaction, to specify the causes of dropout, and to determine the most appropriate authors on dropout by means of literature and different databases. Conclusions It is concluded that, are five main major components would be behind university dropout: student adaptation, personality, socio-economic level, teacher–student relationship, and quality in university education. With them come certain sub-causes that must be taken into account for a better understanding of the reasons for university dropout, such as demotivation, low self-esteem, frustration, pregnancy, among others, reasons why their study is essential for their future eradication.